Role of Electrical Impedance Tomography in Clinical Practice in Pediatric Respiratory Medicine. (25th December 2013) - Durlak, Wojciech; Kwinta, Przemko
Abstract : This paper summarizes current knowledge about electrical impedance tomography (EIT) and its present and possible applications in clinical practice in pediatric respiratory medicine. EIT is a relatively new technique based on real-time monitoring of bioimpedance. Its possible application in clinical practice related to ventilation and perfusion monitoring in children has gaine increasing attention in recent years. Most of the currently published data is based on studies performed on small and heterogenous groups of patients. Thus the results need to be corroborated in future well-designed clinical trials. Firstly a short theoretical overview summarizing physical principles and main advantages and disadvantages is provided. It is followed by a review of the current data regarding EIT application in ventilation distribution monitoring in healthy individuals. Finally the most important studies utilizing EIT in ventilation and perfusion monitoring in critically ill newborns and children are outlined.